43 ways to finance your feature film : a comprehensive analysis of film finance - Cones, John W. (Southern Illinois University Press, 2008)
Author Cones breaks financing options down into six main areas: gifts and grants, investor financing, domestic government subsidies and tax incentive programs, lender financing, international finance options, and studio or industry financing. Beginning with the forms of financing most likely to be accessible to independent feature film producers, Cones proceeds to other forms that become increasingly available as the producer's career matures. He provides specific, concise information regarding the many possible strategies and lists the distinct pros and cons of each strategy. Cones also counters much of the bad advice being provided by pseudoprofessional film finance consultants and points out scams that may separate unwary film producers from their money. Although the book focuses on financing feature films, much of its information is relevant to the financing of other kinds of projects, such as short films, documentaries, videos, and multimedia and theatrical endeavors.--From publisher description.